Very low monomethyl fumarate exposure via human milk: a case report—a contribution from the ConcePTION project - Van Neste, Martje; Nauwelaerts, Nina; Ceulemans, Michael; Cuppers, Benedikte; Annaert, Pieter; Smits, Anne; Allegaert, Karel (Frontiers in Public Health, 2024)
Introduction: While breastfeeding is recommended, knowledge regarding medicine transfer to human milk and its safety for nursing infants is limited. Only one paper has previously described dimethyl fumarate (DMF) transfer during breastfeeding in two patients at 5 and 6 months postpartum respectively. The current case report describes maternal pharmacokinetic data of monomethyl fumarate (MMF), the active metabolite of DMF, and infant exposure estimations of MMF at 3 months postpartum. Methods: A 32-year-old Caucasian woman started DMF therapy (120 mg, 2x/day) for multiple sclerosis at 3 months postpartum, after weaning her infant from breastfeeding. On day 99 after birth, the patient collected 4 milk samples over 24 h after 6 days of treatment at initial dose. Additionally, a single maternal blood sample was collected to calculate the milk-to-plasma ratio. The samples were analyzed using a liquid chromatography coupled with mass spectrometry method. Results: The measured steady-state concentrations of MMF in the human milk samples had a wide range (5.5 -83.5 ng/mL). Estimated daily infant dosage values for MMF, calculated with 150 and 200 mL/kg/day human milk intake, were 5.76 and 7.68 µg/kg/day and the relative infant doses were 0.16 and 0.22%. The observed mean milk-to-plasma (M/P) ratio was 0.059, similar to the M/P ratio predicted by the empirical Koshimichi model (0.06). Discussion: Combining this case report with the two other previously described cases, the estimated infant exposure is low, be it with relevant intra-and inter-patient variability. Research should further focus on infant exposure and safety.